Dynamic analysis of train and bridge in crosswinds based on a coupled wind-train-track-bridge model. Issue 5 (April 2023) - Wu, Jinfeng; Cai, CS; Li, Xiaozhen; Liu, Dejun
The dynamic performance and safety of both the train and the bridge are great concerns for long-span bridges subjected to crosswinds. For railway bridges, there is track laid on the bridge deck. The wind, train, track, and bridge subsystems form a complicated coupling system. This paper presents the dynamic responses of both the train and the bridge under crosswinds based on a wind-train-track-bridge coupled model, in which the vibration effect of the track structure involved in the coupling system is especially considered. For studying the dynamic responses of both the train and the bridge, models of railway vehicle dynamics are used for the train and a three-dimensional finite element model is used for the bridge. The train-track interaction and the track-bridge interaction are respectively considered. The wind action on the train and the bridge consists of a steady-state force and an unsteady-state force. Based on an in-situ test, the proposed numerical wind-train-track-bridge model involving the vibration effect of the track is validated. Then, the application of this proposed model on a long-span cable-stayed bridge on the Shanghai-Suzhou-Nantong HSR (high-speed railway) is presented as a case study. The typical running train and track currently serving in the Chinese railway transportation system are modeled in this study. Excitations from track irregularities are also taken into account. Finally, with the proposed wind-train-track-bridge coupled model, the dynamic performance of both the train and the bridge subjected to crosswinds are investigated.